Metagenomic next-generation sequencing diagnoses Talaromyces marneffei infections: case report and review - Xu, Shu; Ding, Yi; Li, Mengshuo; Lin, Yong; Wang, Xiaoyue; Liu, Na; Zhang, Lihua; Xu, Ting (The Journal of Infection in Developing Countries, 2025)
Introduction: Talaromyces marneffei is a pathogenic dimorphic fungus known for causing severe opportunistic infections that can be life-threatening. The fungus is most commonly found in Southeast Asia and southern China. Case report: This case report describes the case of a young male patient infected with T. marneffei who was neither human immunodeficiency virus (HIV)-positive nor possessed anti-IFN-γ antibodies, and who resided outside the typical endemic regions. The patient developed cough and sputum three months after the removal of the left arm fracture fixator, and was initially misdiagnosed with tuberculosis; however, the response to anti-tuberculosis treatment was not good. The diagnosis of subsequent recurrence was unknown. The condition recurred during the illness, and he was ultimately diagnosed with talaromycosis via metagenomic next-generation sequencing (mNGS). The patient's condition improved after appropriate treatment with liposomal amphotericin B. Conclusions: Previous studies have found that T. marneffei infections are concentrated in patients with acquired immunodeficiency syndrome due to HIV infection, and in anti-IFN-γ antibody-positive patients. However, infections are increasing in individuals who are not immunosuppressed and are often misdiagnosed and underdiagnosed during the initial course of the disease. Therefore, clinicians should be aware that mNGS is an effective technique for detecting T. marneffei infection in non-endemic areas where they encounter non-HIV infected patients. This case report aims to raise the awareness of physicians regarding this rare disease in non-endemic areas and non-HIV patients.